Differences in Multicomponent Pharmacokinetics, Tissue Distribution, and Excretion of Tripterygium Glycosides Tablets in Normal and Adriamycin–Induced Nephrotic Syndrome Rat Models and Correlations With Efficacy and Hepatotoxicity - Wu, Wei; Cheng, Rui; Boucetta, Hamza; Xu, Lei; Pan, Jing–ru; Song, Min; Lu, Yu–ting; Hang, Tai–jun (Frontiers in Pharmacology, 2022)
Abstract: Tripterygium glycoside tablets (TGT) are widely used for treating nephrotic syndrome (NS), but hepatotoxicity is frequently reported. The presence of underlying disease(s) can alter the disposition of drugs and affect their efficacy and toxicity. However, no studies have reported the impact of NS on the ADME profiles of TGT or its subsequent impact on the efficacy and toxicity. Thus, the efficacy and hepatotoxicity of TGT were evaluated in normal and NS rats after oral administration of TGT (10 mg/kg/day) for four weeks. The corresponding ADME profiles of the six key TGT components (triptolide (TPL), wilforlide A (WA), wilforgine (WFG), wilfortrine (WFT), wilfordine (WFD), and wilforine (WFR)) were also measured and compared in normal and NS rats after a single oral gavage of 10 mg/kg TGT. Canonical correlation analysis (CCA) of the severity of NS and the in vivo exposure of the six key TGT components was performed to screen the anti–NS and hepatotoxic material bases of TGT. Finally, the efficacy and hepatotoxicity of the target compounds were evaluated in vitro. The results showed that TGT decreased the NS symptoms in rats, but caused worse hepatotoxicity under the NS state. Significant differences in the ADME profiles of the six key TGT components between the normal and NS rats were as follows: higher plasma and tissue exposure, lower urinary and biliary excretion, and higher fecal excretion for NS rats. Based on CCA and in vitro verification, TPL, WA, WFG, WFT, WFD, and WFR were identified as the anti–NS material bases of TGT, whereas TPL, WFG, WFT, and WFD were recognized as the hepatotoxic material bases. In conclusion, NS significantly altered the ADME profiles of the six key TGT components detected in rats, which were related to the anti–NS and hepatotoxic effects of TGT. These results are useful for the rational clinical applications of TGT.